A Challenging Case of Acute Mercury Toxicity - Ali Nayfeh; Thamer Kassim; Noor Addasi; Faysal Alghoula; Christopher Holewinski; Zachary Depew (Case Reports in Medicine)
Background. Mercury exists in multiple forms: elemental, organic, and inorganic. Its toxic manifestations depend on the type and magnitude of exposure. The role of colonoscopic decompression in acute mercury toxicity is still unclear. We present a case of acute elemental mercury toxicity secondary to mercury ingestion, which markedly improved with colonoscopic decompression. Clinical Case. A 54-year-old male presented to the ED five days after ingesting five ounces (148 cubic centimeters) of elemental mercury. Examination was only significant for a distended abdomen. Labs showed elevated serum and urine mercury levels. An abdominal radiograph showed radiopaque material throughout the colon. Succimer and laxatives were initiated. The patient had recurrent bowel movements, and serial radiographs showed interval decrease of mercury in the descending colon with interval increase in the cecum and ascending colon. Colonoscopic decompression was done successfully. The colon was evacuated, and a repeat radiograph showed decreased hyperdense material in the colon. Three months later, a repeat radiograph showed no hyperdense material in the colon. Conclusion. Ingested elemental mercury can be retained in the colon. Although there are no established guidelines for colonoscopic decompression, our patient showed significant improvement. We believe further studies on this subject are needed to guide management practices.